THE BUHARI ADMINISTRATION AND THE MORTGAGE SECTOR: AN IMPACT ANALYSIS - Ojo Idowu Akinwumi; Sunday Aideloje (International Studies Journal)
This paper holds the opinion that the President Buhari administration made significant efforts to address the housing deficit that his administration inherited based on the analysis provided thus far. To put it another way, the mortgage sector in Nigeria had a housing deficit as its nature and character before the presidency of President Buhari, and the mortgage sector in Nigeria was significantly impacted by the presidency of President Buhari. In the eight years of the Buhari administration, the Federal Mortgage Bank of Nigeria (FMBN) has achieved record-breaking results. Between 2015 and 2023, the Bank surpassed all prior performance benchmarks across all corporate indicators. This includes raising money for the National Housing Fund (NHF) Scheme, disbursing mortgage loans, and providing financing for housing construction. The National Housing Fund (NHF) Scheme was historically optimized as a source of long-term, low-cost financing to support the provision of affordable housing to Nigerians